2005
DOI: 10.1123/jsm.19.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Occupational Commitment, Intention to Leave, and Perceived Performance of Intercollegiate Coaches

Abstract: Three hundred twenty-eight intercollegiate coaches (men = 240, women = 88; Division I = 156, Division III = 172) responded to a questionnaire measuring commitment to their university and coaching occupation, intention to leave the organization and occupation, their team standings, and perceptions of their performance. The variables of division, gender, and marital/lifestyle status affected neither organizational nor occupational commitments. Organizational commitments of affective, normative, continuance: high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 23 publications
6
69
1
11
Order By: Relevance
“…The effects of turnover, including cost (Turner, 2001) and impact on team performance (McQueary, 1997) indicate a strong reason to retain coaches by focusing on the creation of an open, collegial, and trusting environment (Chelladurai & Ogasawara, 2003). Furthermore, Turner and Chelladurai (2005) found it much more cost effective to retain a competent coach than to replace and train a new one. Additionally, researchers have shown that trust develops over a period of time (Baier, 1986;Jones & George, 1998).…”
Section: Rationale For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of turnover, including cost (Turner, 2001) and impact on team performance (McQueary, 1997) indicate a strong reason to retain coaches by focusing on the creation of an open, collegial, and trusting environment (Chelladurai & Ogasawara, 2003). Furthermore, Turner and Chelladurai (2005) found it much more cost effective to retain a competent coach than to replace and train a new one. Additionally, researchers have shown that trust develops over a period of time (Baier, 1986;Jones & George, 1998).…”
Section: Rationale For the Studymentioning
confidence: 99%
“…With greater scrutiny over expenditures and organizational outcomes, the need to understand how trust manifests in intercollegiate athletic departments is paramount. While there has been significant examination of organizational behavior in intercollegiate sports, scant research has focused on trust in college athletic departments (Chelladurai & Ogasawara, 2003;Dirks, 2000;Turner, 2001;Turner & Chelladurai, 2005).…”
mentioning
confidence: 99%
“…Sports studies using the occupational affective scale with other occupational variables have also found positive correlations with job satisfaction (Pack, 2005) and career satisfaction (Cunningham, Sagas, Dixon, Kent, & Turner 2005) and a negative correlation with turnover intentions (Turner & Chelladurai, 2005). The findings have important implications for organizations seeking to keep employees satisfied while reducing job-related hiring and retention costs (Turner & Chelladurai, 2005).…”
Section: Technological Linkagesmentioning
confidence: 97%
“…Sports studies using the occupational affective scale with other occupational variables have also found positive correlations with job satisfaction (Pack, 2005) and career satisfaction (Cunningham, Sagas, Dixon, Kent, & Turner 2005) and a negative correlation with turnover intentions (Turner & Chelladurai, 2005). The findings have important implications for organizations seeking to keep employees satisfied while reducing job-related hiring and retention costs (Turner & Chelladurai, 2005). Researchers have examined the construct with various occupational groups such as university athletic administrators (Pack, 2005;Turner & Chelladurai, 2005), fitness club employees (Chang & Chelladurai, 2003), and sport administration college interns (Cunningham, Sagas, Dixon, Kent, & Turner, 2005).…”
Section: Technological Linkagesmentioning
confidence: 99%
See 1 more Smart Citation